Effects of Processing on the Proximate Composition, Mineral Content and the Phytochemical Analysis of Groundnut Seeds (Arachis hypogeae) - Sanni, Joseph Adaviruku; Sanni, Grace Omayoza; Awoniyi, Rufus Ranmilowo; Osanyinlusi, Remi; Richards, Yvonne Ego; Adesina, Goodness Inioluwa; Adenuga, Ore-ofe Oluwatoyin; Apata, Stella Ayomikun; Ekun, Oluwafemi Emmanuel (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Effect of processing on the nutritional composition of groundnut seeds were carried out using standard analytical methods. Raw, boiled and fried groundnut seeds were analyzed for proximate composition, mineral contents, and phytochemical screening. The result reported that the raw, boiled, and fried contains (5.357±0.190%, 4.545±0.050% and 3.896±0.015%, moisture contents), (2.401±0.011%, 3.225±0.004% and 2.816±0.001%, ash contents), (46.591±0.001%, 25.333±0.003% and 48.012±0.953%, crude fat), (4.126±0.887%, 15.001±0.030% and 7.692±0.002%, crude fibre), (19.520±0.040%, 21.580±0.040% and 23.540±0.000%, crude protein), (22.005±0.587%, 30.316±0.056% and 14.044±0.939%, carbohydrate) respectively. A significant difference was observed. Processing has significant effects on the mineral components of the seeds. The results revealed that raw, boiled and fried contains (56.900mg/100g, 48.400mg/100g and 35.00mg/100g Sodium), (0.215mg/100g, 0.185mg/100g and 0.540mg/100g Zinc), (65.500mg/100g, 42.700mg/100g and 25.500mg/100g Magnesium), (0.218mg/100g, 0.230mg/100g and 0.230mg/100g Iron), (0.250mg/100g, 0.110mg/100g and 0.100mg/100g Manganese). The phytochemical screening shows the presence of alkaloids, carbohydrates and proteins in all the samples and the result reveals that processing does not really have effect on phytochemical constituents. The investigation shows that fresh groundnut is a good source of mineral content, while raw and processed groundnut is a good source of some phytochemical constituents and processed groundnut is a good source of protein, fat, and carbohydrate with high nutritional value.